Supervision of Educational Functions on Television Films During the Covid 19 Pandemic - Fetrimen, Fetrimen; Khuluqo, Ihsana El; Kodri, Safrul (Journal of Education Reseach and Evaluation, 2022)
During the Covid-19 pandemic, television can be used as an efficient and effective educational medium. However, television broadcasts are often dangerous and can be followed by students. Supervision of films watched by children is essential because shows that are not by age classification can affect behavior. One of the negative impacts is that it contains violence that children easily imitate. The purpose of this study is to analyze the educational function of television films during the covid 19 pandemic. This research is a type of quantitative research. The method used in this research is a survey method. The survey was administered to 34 volunteers who watched and supervised television films. The instrument used in data collection is a questionnaire. The data analysis technique used is descriptive qualitative and quantitative analysis. The study results are television films that do not have a telephone number as much as 32%. A discrepancy between telephone calls and the sensor results is as much as 37%. Do not make revisions by the recommendations of the Film Censorship Institute as much as 3%. Meanwhile, voiceovers were found to be 25% and 3% of expired phone calls.